Georgia : Technical Assistance Report-Updating the Balance Sheet and Quantifying Fiscal Risks From Climate Change. (IMF Staff Country Reports; Country Report ;, 2022)
The Georgian Ministry of Finance (MoF) has continued to progress its analysis and reporting of fiscal risks, with its annual Fiscal Risk Statement (FRS) becoming the leading example in the region. In addition to detailed discussions of risks from SOEs and the balance sheet, amongst other, the December 2020 FRS included for the first time a qualitative discussion on the fiscal risks from climate change. Looking ahead, the government has committed to strengthening that further with the inclusion of quantitative estimates in the 2022 version of the FRS. This report provides the tools and analytical approaches to support that, as well as an update to the public sector balance (PSBS) sheet to identify the impact of the pandemic.